Investors' Reactions to Management Earnings Guidance: The Joint Effect of Investment Position, News Valence, and Guidance Form - HAN, JUN; TAN, HUN‐TONG (Journal of Accounting Research, 2010)
ABSTRACT We report the results of an experiment that shows that investors' earnings‐ and investment‐related judgments are jointly influenced by their investment position (long versus short), the news valence of guidance issued by management, and the amount of ambiguity in the guidance. Prior research indicates that guidance form (point versus range) has no effect on investors' earnings estimates made in reaction to management guidance. We extend this research by showing that guidance form matters, conditional on investment position and news valence. Similarly, prior research indicates that investors who hold long (short) positions in a stock are more optimistic (pessimistic) about the company's prospects. We extend this research by showing that the effect of investment position documented in prior studies is conditional on news valence and guidance form. We contribute to prior literature on the effects of investment position and guidance form by delineating boundary conditions for each of these effects.